Assessment of the use of the Internet and social media among people with bladder cancer and their carers, and the quality of available patient‐centric online resources: a systematic review. (23rd April 2019) - Tariq, Amina; Khan, Shanchita R.; Vela, Ian; Williams, Elizabeth D.
Abstract : Objective: To conduct a systematic synthesis of the literature evaluating the use of the Internet and social media by people with bladder cancer (BCa) and their carers, and to synthesize the evidence on the quality of available online resources for patients with BCa. Methods: We selected studies published between January 2000 and September 2018, written in the English language and meeting the inclusion criteria. Data sources included PubMed, PsycINFO, EMBASE, Web of Science and Scopus. Results: A total of 15 studies were included in the review. Four studies explored patterns of Internet use among patients with BCa, five studies investigated social media use related to BCa and six studies evaluated the quality of online resources available for patients with BCa. Evidence in all these three dimensions was limited in its ability to establish rigorously if use of the Internet, social media and online resources for BCa is effective in improving the care outcomes for patients with BCa. Conclusion: Our review emphasizes the forgotten status of BCa by establishing that, despite its high global incidence, it remains underrepresented in the building of evidence on patient information needs and the possible role of online spaces. Our synthesis establishes that further research is needed to examine the full impact of online information and social media use on the health management of people with BCa.